2020
DOI: 10.3390/jcm9072067
|View full text |Cite
|
Sign up to set email alerts
|

Home Respiratory Polygraphy is Useful in the Diagnosis of Childhood Obstructive Sleep Apnea Syndrome

Abstract: The utility of home respiratory polygraphy (HRP) was assessed as an alternative to polysomnography (PSG) in the diagnosis of childhood obstructive sleep apnea syndrome (OSAS). PSG was indicated only in patients with concomitant disease or where HRP results were questionable. The follow-up period was 1 year. We recorded clinical and anthropometric data, physical examination findings, respiratory variables, severity level and choice of therapy. We assessed 121 children, 70 boys and 51 girls, with mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
12
2
1
Order By: Relevance
“…Moreover, the high number of sensors connected to the child along with having to sleep outside of home makes PSG also especially uncomfortable and inconvenient for patients and caretakers [11,12]. These drawbacks have motivated the search for alternatives to diagnose pediatric OSA and to study its consequences while reducing the number of signals required for the diagnosis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the high number of sensors connected to the child along with having to sleep outside of home makes PSG also especially uncomfortable and inconvenient for patients and caretakers [11,12]. These drawbacks have motivated the search for alternatives to diagnose pediatric OSA and to study its consequences while reducing the number of signals required for the diagnosis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…9 By providing more accessible sleep consultation and testing for this population through telehealth, pediatric sleep health practitioners can support the already tremendous efforts of multidisciplinary teams caring for patients with autism spectrum disorder. 4 The successful initial use of HSAT in this patient, another adaptation put in place due to the pandemic, highlights its utility as a feasible alternative to polysomnography, [3][4][5] particularly in children with atypical neurodevelopment who already struggle with sleep. [9][10][11] The failed postoperative HSAT demonstrates the difficulties with utilizing this technology in children.…”
Section: Discussionmentioning
confidence: 96%
“…2 However, studies that followed the publication of this guideline demonstrated minimal artifact and good sensitivity and specificity when evaluating moderate/severe sleep-disordered breathing, 3 particularly in older children. 4,5 More research is needed to explore this technology in children.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocated the use of PSG only in patients with concomitant disease or where Home Respiratory Polysomnography (HRP) results are inconclusive. 8 9 Nagappa et al in a recent meta-analysis concluded that in ambulatory patients one should use the STOP (snoring, tiredness, observed apnea, and high blood pressure)–Bang (body mass index, age, neck circumference, and gender) questionnaire to identify suspected patients with SAS, so that periprocedural management can be more focused and appropriate. 10 This as a screening tool also has been described by several other authors.…”
Section: Discussionmentioning
confidence: 99%